IDENTIFIKASI SPESIES JAMUR PADA RUMAH MAKAN DI KAWASAN STASIUN GUBENG SURABAYA - Ariana, Diah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
IDENTIFIKASI SPESIES JAMUR PADA RUMAH MAKAN DI KAWASAN STASIUN GUBENG SURABAYA Diah Ariana, ST, MKesdiah0101@gmail.comProdi D3 Analis Kesehatan UM Surabaya                                                                        Abstract Gubeng Station Surabaya is a railway station (Railway) is the largest in Surabaya and the departure KA (Railway) main Surabaya. City restaurant in the station Gubeng Surabaya is the proposition to consume food and beverages for the passengers and employees at Station Gubeng Surabaya. Not all rooms in Surabaya Gubeng station or air-cooled rooms and well ventilated or air conditioned if the room should be sealed room for the cool room conditions. While in the room that is not refrigerated room is generally open to the wind and air and the room was not stuffy. From both of these can affect dust in the air entering the space station that are not refrigerated or cooled. Until now, this has not been studied how the room is viewed from the existence of diverse species of mangingat every day do the activity in any room especially the restaurants in the station surabaya Gubeng. This type of research is descriptive. The population sample was dust in the air contained in the restaurants in the station Gubeng Surabaya. Time studies carried on from the 6th of January to complete. Variable research is mushroom species and its operational definition is a genus of fungus that is found in a restaurant in the station Gubeng Surabaya based on the results of examination by means cultured or breed with SDA media. The results of this research are as much as 100% of the restaurants in the area Gubeng station Surabaya contaminated mushroom species. There are 3 types of fungal species were identified, namely 26 Aspergillus sp. (86.6%), 3 species of Microsporum sp. (9.99%), and 1 species of Penicillium sp. (3.33%). Mushrooms of the most contaminated in the restaurant at the station Gubeng Surabaya is Aspergillus sp.Keyword : fungi, Gubeng Station Surabaya